Hospitalization of Pediatric Patients with Oral and Pharyngeal Cancer in Brazil’s National Health System from 2008 to 2023 - Ricardo Barbosa Lima; Stefany Santana Bispo; Nathan Henrique de Santana Fontes; Everton Guilherme Jesus dos Santos; Talita Silva Sobral; Aquiles Sales Craveiro Sarmento; Breno Gustavo do Nascimento Gomes; Silas Zambaldi Garcia (Revista Brasileira de Cancerologia)
Introduction: Pediatric cancer patients often need inpatient admissions due to treatment or complications, but this variable was not systematically evaluated in Brazil’s public health services. Objective: To evaluate inpatient admissions of children and adolescents with oral and pharyngeal cancer in the Brazilian public healthcare system. Method: Population-based approach study from 2008 to 2023 of the annual hospitalizations recovered and normalized per 1,000,000 inhabitants aged 0-19 years (person-year incidence), in addition to the annual deaths, hospital mortality (%), length of hospital stay (days), costs (R$), and conditions (elective or urgent). The significance level was adjusted to 5%, according to Prais-Winsten generalized linear regression models. Results: From 2008 to 2023, 24,662 inpatient admissions were approved, 50.5% of which classified as urgent. The incidence was 395 per 1,000,000 0-19 aged children. During this period, 626 deaths were reported, representing 2.5% of all hospitalizations. Moreover, the mean length of stay was 5.8 days and the mean cost was R$ 1,526.87. There was a decreasing time trend in the incidence of hospitalizations of children and adolescents (both p < 0.001). The incidence and hospital mortality were significantly lower among children and adolescents compared to other age groups (all p < 0.001). Conclusion: Over the last 16 years, an important number of inpatient admissions of children and adolescents with oral and pharyngeal cancer in the Brazilian public healthcare system was recorded, revealing specific patterns of hospital morbidity.